Angiotensin II, blood–brain barrier permeability, and microglia interplay during the transition from pre-to hypertensive phase in spontaneously hypertensive rats - Makuch-Martins, Mariana; Vieira-Morais, Camilla G.; Perego, Sany M.; Ruggeri, Adriana; Ceroni, Alexandre; Michelini, Lisete C. (Frontiers in Physiology, 2024)
Background Hypertension is characterized by upregulation of the renin–angiotensin system, increased blood–brain barrier (BBB) permeability, microglia activation within autonomic nuclei, and an intense sympathoexcitation. There is no information on the interplay of these events during the development of neurogenic hypertension. We sought to identify the interaction and time-course changes of Ang II availability, barrier dysfunction, microglia activation, and autonomic imbalance within autonomic areas during the development of neurogenic hypertension. Methods Sequential changes of hemodynamic/autonomic parameters, BBB permeability, microglia structure/density (IBA-1), and angiotensin II (Ang II) immunofluorescence were evaluated within the paraventricular hypothalamic nucleus, nucleus of the solitary tract, and rostral ventrolateral medulla of Wistar and spontaneously hypertensive rats (SHRs) aged 4 weeks, 5 weeks, 6 weeks, 8 weeks, and 12 weeks. The somatosensory cortex and hypoglossal nucleus were also analyzed as non-autonomic control areas. Results Increased brain Ang II availability (4th–5th week) was the first observed change, followed by the incipient BBB leakage and increased microglia density (6th week). From the 5th–6th weeks on, BBB leakage, Ang II, and IBA-1 densities increased continuously, allowing a parallel increase in both Ang II-microglia colocalization and the transition of microglial cells from highly ramified in the basal surveillant condition (4th–5th week) to shorter process arbors, fewer endpoints, and enlarged soma in the disease-associate condition (6th week to the 12th week). Simultaneously with increased Ang II-microglia colocalization and microglia morphologic phenotypic changes, sympathetic activity and pressure variability increased, autonomic control deteriorated, and blood pressure increased. These responses were not specific for autonomic nuclei but also occurred at a lower magnitude in the somatosensory cortex and hypoglossal nucleus, indicating the predominance of hypertension-induced effects on autonomic areas. No changes were observed in age-matched controls where Ang II density did not change. Conclusion Brain Ang II density is the initial stimulus to drive coordinated changes in BBB permeability and microglial reactivity. Increased BBB dysfunction allows access of plasma Ang II and increases its local availability and the colocalization and activation of microglial cells. It is a potent stimulus to augments vasomotor sympathetic activity, autonomic imbalance, and pressure elevation during the establishment of hypertension.